The Accuracy of Empirical Antibiotic Treatment for Periprosthetic Joint Infections in Total Shoulder and Knee Arthroplasties - Katrin Freller; Hannah Punz; Clemens Schopper; Tobias Gotterbarm; Antonio Klasan; Stella Stevoska (Antibiotics)
Introduction: Periprosthetic joint infections (PJIs) remain a major challenge in orthopedic and trauma surgeries. The microbial resistance profiles and the optimal choice of empirical antibiotic therapy in shoulder arthroplasty revision are less well characterized compared to those in knee or hip arthroplasty revision. Materials and Methods: This retrospective study constitutes a novel comparative analysis, providing valuable insights into the presence of joint-specific pathogen resistance and the empirical treatment accuracy of shoulder and knee arthroplasties. A review of all the revision cases following primary shoulder and knee arthroplasties conducted between January 2012 and December 2023 was performed. Cases that required revision because of PJIs were identified, and microbial cultures were analyzed to determine the presence of pathogens and their resistance profiles. Results: The most administered postoperative empirical antibiotics were cefuroxime and amoxicillin–sulbactam. A statistically significant difference in the prevalence of anerobic pathogens was observed between total shoulder arthroplasty and knee arthroplasty. Furthermore, a statistically significant difference was observed in the sensitivities of pathogens to metronidazole (p < 0.001) and erythromycin (p = 0.014). Conclusions: This study demonstrates microbiological and antimicrobial resistance differences between PJI TSA and TKA cases.